2003
DOI: 10.1134/1.1627432
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of low ferrialuminosilicate sanidine

Abstract: Iron-containing potassium feldspar crystals are prepared using the hydrothermal synthesis in an alkaline medium at temperatures ranging from 500 to 526°C. The crystal structure of the synthetic potassium feldspar is refined [Ital Structures diffractometer, MoKalpha radiation, 1327 unique reflections with F > 4sigma(F), anisotropic approximation, R(F) = 0.044]. It is established that, under the given preparation conditions, the synthesis leads to the formation of the monoclinic modification with the following u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, Ba in martian meteorites has not been detected above 0.05 apfu and only 0.006% of the ~1000 martian meteorite feldspars contained any measurable Ba (Papike et al 2009;Santos et al 2015;Wittmann et al 2015;Nyquist et al 2016;Hewins et al 2017). Additionally, sanidine can incorporate significant Fe 3+ in the tetrahedral site, up to 0.698 Fe 3+ apfu (Kuehner and Joswiak 1996;Linthout and Lustenhouwer 1993;Lebedeva et al 2003). However, when the abundance of Fe 3+ exceeds 0.1 apfu, the b unit-cell parameter increases beyond 13.05 Å and noticeably deviates from the trends shown in the alkali feldspar section below (Best et al 1968;Lebedeva et al 2003).…”
Section: Feldsparmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ba in martian meteorites has not been detected above 0.05 apfu and only 0.006% of the ~1000 martian meteorite feldspars contained any measurable Ba (Papike et al 2009;Santos et al 2015;Wittmann et al 2015;Nyquist et al 2016;Hewins et al 2017). Additionally, sanidine can incorporate significant Fe 3+ in the tetrahedral site, up to 0.698 Fe 3+ apfu (Kuehner and Joswiak 1996;Linthout and Lustenhouwer 1993;Lebedeva et al 2003). However, when the abundance of Fe 3+ exceeds 0.1 apfu, the b unit-cell parameter increases beyond 13.05 Å and noticeably deviates from the trends shown in the alkali feldspar section below (Best et al 1968;Lebedeva et al 2003).…”
Section: Feldsparmentioning
confidence: 99%
“…Additionally, sanidine can incorporate significant Fe 3+ in the tetrahedral site, up to 0.698 Fe 3+ apfu (Kuehner and Joswiak 1996;Linthout and Lustenhouwer 1993;Lebedeva et al 2003). However, when the abundance of Fe 3+ exceeds 0.1 apfu, the b unit-cell parameter increases beyond 13.05 Å and noticeably deviates from the trends shown in the alkali feldspar section below (Best et al 1968;Lebedeva et al 2003). Hewins et al (2017) reported as much as 0.09 Fe 3+ apfu in martian meteorite feldspar, an abundance that is unlikely to be detectable by examination of unit-cell parameters.…”
Section: Feldsparmentioning
confidence: 99%
“…First, although two elemental analyses (inductively coupled plasma mass spectrometry and x-ray fluorescence) did determine that there were trace amounts of iron in K3, there was still some doubt as to whether the 1.77 eV phosphorescence was coming from Fe 3+ ions or not. Second, although one can deduce from x-ray diffraction data that the geometry of the four anions around the Fe 3+ ions in T1 sites is not very different from the average geometry for T1 sites (see Nadezhina et al 1993, Short 2003, the precise geometry is not known. One must assume that the geometry has a symmetry axis that coincides with one of the dipole directions deduced from the polarization data.…”
Section: Introductionmentioning
confidence: 99%
“…This is because Fe exists almost exclusively as Fe 3+ in the tetrahedra framework replacing Al in K-feldspars (Michoulier and Gaite, 1972;Behrens et al, 1990;Ackermann et al, 2005). The Fe member of the feldspar group, ferrisanidine, which has been synthesized for decades (Faust, 1936;Wones and Appleman, 1963;Lebedeva et al, 2003;Taroev et al, 2008), was recently discovered in nature (Shchipalkina et al, 2019). However, most of the Fe-bearing alkali feldspars studied are K-rich sanidine that crystalized at high temperature, and the Fe concentrations of alkali feldspars from slow-cooled granite or pegmatite are significantly lower (Smith and Brown, 1988, pp.…”
Section: Formation Of the Magnetite Filmmentioning
confidence: 99%